The Pattern of Adipose Tissue Accumulation during Early Infancy Provides an Environment for the Development of Dengue Hemorrhagic Fever. - Daniel H Libraty; Pengyan Wang; Zhiru Guo; Venelle Bigcas; Job D Brion; Rosario Z Capeding (Public Library of Science (PLoS), 2015)
BACKGROUND:Dengue is the most prevalent arthropod-borne viral illness in humans with half of the world's population at risk. During early infancy, severe dengue can develop after a primary dengue virus infection. There has been a clinical observation that severe dengue during the first year of life is seen only in chubby infants. METHODOLOGY/PRINCIPAL FINDINGS:We examined the associations between the development of severe dengue and adipose tissue accumulation patterns during the first year of life in a prospective observational clinical study of infants and dengue virus infections. We found that adipose tissue contains two potential targets for dengue virus infection and production- adipocytes and adipose tissue macrophages. During the first year of life, total body adiposity and visceral adipose tissue stores were at their highest levels in early infancy. Early infancy was also characterized by a relative decrease in alternatively activated (anti-inflammatory) macrophages, and a relative increase in circulating pro-inflammatory cytokines. CONCLUSIONS/SIGNIFICANCE:The data has been used to propose a model where the adipose tissue accumulation pattern and pro-inflammatory environment during early infancy provide the conditions for the potential development of severe dengue in immune-susceptible infants.